Nonlinear Systems and Circuits in Internal Combustion Engines : Modeling and Control /: Modeling and Control. (2017) - Taglialatela-Scafati, Ferdinando; Lavorgna, Mario; Mancaruso, Ezio; Vaglieco, Bianca Maria
No abstract available